ENHANCING WATER AND FERTILIZER SAVING WITHOUT COMPROMISING RICE YIELD THROUGH INTEGRATED CROP MANAGEMENT - I.P. Wardana; A. Gania; S. Abdulrachman; P.S. Bindraban; H. van Keulen (Indonesian Agency for Agricultural Research and Development, 2010)
Water and fertilizer scarcity amid the increasing need of rice production challenges today’s agriculture. Integrated crop management (ICM) is a combination of water, crop, and nutrient management that optimizes the synergistic interaction of these components aiming at improving resource use efficiency, i.e. high productivity of water, land, and labor. The objectives of the study were to investigate the effects of crop establishment method, organic matter amendment, NPK management, and water management on yield of lowland rice. Five series of experiments were conducted at Sukamandi and Kuningan Experimental Stations, West Java. The first experiment was focused on crop establishment method, i.e. plant spacing and number of seedlings per hill. The second, third, and fourth experiments were directed to study the effect of NPK and organic matter applications on rice yield. The fifth experiments was designed to evaluate the effect of water management on rice yield. Results showed that 20 cm x 20 cm plant spacing resulted in the highest grain yield for the new plant type rice varieties. Organic matter and P fertilizer application did not significantly affect grain yield, but the yield response to P fertilization tended to be stronger with organic matter amendment. Split P application did not significantly increase grain yield. The use of a scale 4 leaf color chart reading resulted in a considerable N fertilizer saving without compromising rice yield. Intermittent irrigation technique saved water up to 55% without affecting yields, resulting in a 2-3 times higher water productivity.